Beyond Dermatological Findings: Multisystem Involvement in Prolidase Deficiency - Ezgi Yalcin Gungoren; Zeynep Meric; Asena Pinar Sefer; Asuman Deveci Ozkan; Salim Can; Royala Babayeva; Nurhan Kasap; Ercan Nain; Esra Ozek Yucel; Ayca Kiykim; Sevgi Bilgic-Eltan; Ayse Deniz Yucelten; et al. (Turkish Archives of Pediatrics)
Objective: Prolidase deficiency is a metabolic and immunological disorder that is inherited in an autosomal recessive manner. In prolidase deficiency, a broad spectrum of differences is observed in patients, ranging from asymptomatic to multisystem involvement. There is scarce information in the literature on the atypical features and immunophenotypes of this disease. Aim of this study is to present 4 new cases to provide information on the rare features of the disease and to raise awareness.